PROPOSALS FOR CALCULATING COMPRESS, COMPRESS-BEND AND CURVED CONCRETE ELEMENTS - and (Municipal economy of cities (Technical science), 2013)
The calculation of reinforce-concrete non axial compression elements and bending elements on the basis of deformation model. The tasks of calculation of such elements are rationed.